2015
DOI: 10.1039/c4gc01277a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, energy-efficient synthesis of the layered carbide, Al4C3

Abstract: The phase-pure binary aluminium carbide, Al4C3 can be synthesised in vacuo from the elements in 30 minutes via microwave heating in a multimode cavity reactor. The success of the reaction is dependent on the use of finely divided aluminium and graphite starting materials, both of which couple effectively to the microwave field. The yellow-brown powder product was characterised by powder X-ray diffraction, scanning electron microscopy / energy dispersive X-ray spectroscopy thermogravimetric-differential thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 45 publications
1
13
0
2
Order By: Relevance
“…In addition, the Raman spectrum of the C‐enriched region reveals three weak peaks around 493, 718, and 864 cm −1 . These peaks have been attributed to be the A 1g , E g and again A 1g phonon modes of aluminum carbide (Al 4 C 3 ) . It is interesting to note that at each Al 4 C 3 , a weak peak at 521 cm −1 can be detected, which is likely to come from the neighboring Si particles.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, the Raman spectrum of the C‐enriched region reveals three weak peaks around 493, 718, and 864 cm −1 . These peaks have been attributed to be the A 1g , E g and again A 1g phonon modes of aluminum carbide (Al 4 C 3 ) . It is interesting to note that at each Al 4 C 3 , a weak peak at 521 cm −1 can be detected, which is likely to come from the neighboring Si particles.…”
Section: Resultsmentioning
confidence: 96%
“…It was reported that aluminum nitride (AlN) can be formed by the reaction of Al 2 O 3 and carbon at 1400–1800°C in nitrogen or ammonia flow, and the oxidation of AlN is initiated at 850–900°C . In addition, the carbothermal reduction of Al 2 O 3 must be conducted above 2000°C to form Al 4 C 3 , and Al 4 C 3 is found to be stable to 1000°C in air . In our opinion, as Al 2 O 3 particles exist in the pores of the stabilized PAN fibers, it is unlikely they will be in contact with nitrogen to produce AlN during the carbonization.…”
Section: Resultsmentioning
confidence: 84%
“…As the temperature increases, the I D /I G ratio increases from 0.83 to 1.47, and a second-order 2D line appears in the spectrum. A line at ∼ 864 cm −1 , corresponding to the most intense A 1g line of Al 4 C 4 appears in the spectrum of the sample calcined at 1500 • C [29]. Its appearance corresponds to the start of the oxide core carbothermal reduction to aluminum carbide.…”
Section: Almentioning
confidence: 92%